Fetal outcome and recommendations of pregnancies in lupus nephritis in the 21st century. A prospective multicenter study. (November 2016) - Moroni, Gabriella; Doria, Andrea; Giglio, Elisa; Tani, Chiara; Zen, Margherita; Strigini, Francesca; Zaina, Barbara; Tincani, Angela; de Liso, Federica; Matinato, Caterina; Grossi, Claudia; Gatto, Mariele; et al.
Abstract: The aim of this multicenter study was to assess the present risk of fetal complications and the inherent risk factors in pregnant women with lupus nephritis. Seventy-one pregnancies in 61women (59 Caucasians and 2 Asians) with lupus nephritis were prospectively followed between October 2006 and December 2013. All patients received a counselling visit within 3 months before the beginning of pregnancy and were followed by a multidisciplinary team. At baseline mild active nephritis was present in 15 cases (21.1%). Six pregnancies (8.4%) resulted in fetal loss. Arterial hypertension at baseline (P = 0.003), positivity for lupus anticoagulant (P = 0.001), anticardiolipin IgG antibodies (P = 0.007), antibeta2 IgG (P = 0.018) and the triple positivity for antiphospholipid antibodies (P = 0.004) predicted fetal loss. Twenty pregnancies (28.2%) ended pre-term and 12 newborns (16.4%) were small for gestational age. Among the characteristics at baseline, high SLE disease activity index (SLEDAI) score (P = 0.027), proteinuria (P = 0.045), history of renal flares (P = 0.004), arterial hypertension (P = 0.009) and active lupus nephritis (P = 0.000) increased the probability of preterm delivery. Odds for preterm delivery increased by 60% for each quarterly unit increase in SLEDAI and by 15% for each quarterly increase in proteinuria by 1 g per day. The probability of having a small for gestational age baby was reduced by 85% in women who received hydroxychloroquine therapy (P = 0.023). In this study, the rate of fetal loss was low and mainly associated with the presence of antiphospholipid antibodies. Preterm delivery remains a frequent complication of pregnancies in lupus. SLE and lupus nephritis activity are the main risk factors for premature birth. Arterial hypertension predicted both fetal loss and preterm delivery. Based on our results the key for a successful pregnancy in lupus nephritis is a multidisciplinary approach with close medical, obstetric and neonatal monitoring. This entails: a) a preconception evaluation to establish and inform women about pregnancy risks; b) planning pregnancy during inactive lupus nephritis, maintained inactive with the lowest possible dosage of allowed drugs; c) adequate treatment of known risk factors (arterial hypertension, antiphospholipid and antibodies); d) close monitoring during and after pregnancy to rapidly identify and treat SLE flares and obstetric complications. Highlights: Fetal prognosis of SLE pregnancies is improved but is still worse than in healthy women. In our cohort, antiphospholipid antibodies and arterial hypertension are the predictors of fetal loss. Nowadays pre term delivery is the most frequent complication in lupus nephritis pregnancies. SLE and lupus nephritis activity and arterial hypertension predict pre term delivery. SLE mothers treated with hydroxychloquine have low risk of SFGA babies.